Performance of Public Enterprises in Nepal - K.C., Fatta Bahadur (NRB Economic Review, 2003)
Public Enterprises (PEs) have been established in Nepal with multiple goals and responsibilities. Though PEs have assisted in developing the infrastructure and institutional base in the country, these enterprises have neither been functioning in an efficient manner nor been able to perform their assigned roles. Performance analysis, in terms of the financial, economic and social parameters, shows that the Nepalese PEs have not been successful in achieving the financial and economic objectives, and also in providing social benefits to the people at large. Excessive political interference, lack of adequate autonomy and accountability, absence of professionalism, rampant financial indiscipline and conflicting goals have been the main reasons responsible for the dismal performance of PEs in Nepal. However, their performance can be improved by allowing greater autonomy and more accountability by introducing reward and punishment system linked with performance, and by appointing the Chief Executive Officer (CEO) by merit basis. In the absence of such measures, these enterprises need to be either privatized or liquidated. Presently, PEs in Nepal are, no doubt, at the cross-roads. Any delay in implementing reforms (privatizing or liquidating or continuing to operate through restructuring) would be detrimental to the overall health of the national economy.